2018
DOI: 10.1001/jamaoncol.2018.3277
|View full text |Cite
|
Sign up to set email alerts
|

Nab-Paclitaxel and Gemcitabine as First-line Treatment of Advanced or Metastatic Cholangiocarcinoma

Abstract: ClinicalTrials.gov identifier: NCT02181634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 22 publications
6
92
0
1
Order By: Relevance
“…The most frequent especially severe adverse events in this study were from hematologic toxicities, which were mainly attributed to chemotherapy. However, we observed that the incidence of grade 3 or higher thrombocytopenia was much higher than currently reported gemcitabine and cisplatin chemotherapy [4,5,7], whether the addition of nivolumab to chemotherapy deteriorated thrombocytopenia remained unclear. Indeed, thrombocytopenia was a common toxicity of immune checkpoint inhibitors [18][19][20].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most frequent especially severe adverse events in this study were from hematologic toxicities, which were mainly attributed to chemotherapy. However, we observed that the incidence of grade 3 or higher thrombocytopenia was much higher than currently reported gemcitabine and cisplatin chemotherapy [4,5,7], whether the addition of nivolumab to chemotherapy deteriorated thrombocytopenia remained unclear. Indeed, thrombocytopenia was a common toxicity of immune checkpoint inhibitors [18][19][20].…”
Section: Discussionmentioning
confidence: 81%
“…However, this combination regimen confers a limited efficacy, one possible reason is the rich desmoplastic stroma of BTCs, forming a barrier to the delivery of chemotherapeutic drugs in the tumor bed, and resulting in resistance to chemotherapy. Other regimens or strategies, such as gemcitabine and oxaliplatin with or without cetuximab [5], capecitabine plus cisplatin [6], nab-paclitaxel and gemcitabine [7], and small molecule kinase inhibitors targeting FGFR, IDH, MET, Mesothelin, BRCA and other mutated genes, did not show significant improvements of efficacy and survival [8,9].…”
mentioning
confidence: 99%
“…A final gemcitabine-based doublet that was explored in patients with advanced CCA is gemcitabine plus nab-paclitaxel. In 2018, Sahai et al [35] reported the results of a multicenter phase II trial in which 74 patients with advanced CCA were treated with nab-paclitaxel (125 mg/m 2 IV) followed by gemcitabine (1000 mg/m 2 on Days 1, 8, and 15) in 28-day treatment cycles [35] . The regimen was effective, with an ORR of 30% and a median OS of 12.4 months.…”
Section: Gemcitabine-based Doublet Chemotherapymentioning
confidence: 99%
“…[10,11] To date, nab-paclitaxel has been approved by the United States Food and Drug Administration for the treatment of metastatic breast cancer, locally advanced or metastatic non-small cell lung cancer, and metastatic pancreatic cancer. [10,12] Not only that, there is growing evidence that nab-paclitaxel is effective in the treatment of other malignant tumors, [13,14] including STS. [15][16][17] Since January 2019, advanced sarcoma patients have been treated in our hospital (a major sarcoma treatment center in central China) with nab-paclitaxel and gemcitabine.…”
Section: Introductionmentioning
confidence: 99%